Empowerment of Zero Waste Maritime Village Based on Creative Economy in Wirittasi Village, Kusan Hilir, Tanah Bumbu - Syarifah Khusnul Khotimah; Nasruddin; Hanida Aulia Santi; Anastasya Rosyida An-Nafi; Siti Aulia; Akhmad Nabil Arifin; Hardiansyah; Muhammad Fakhruz Zaini; Muhammad Syarif Hidayatullah; Amirul Mukminin; Asse Padly; Ainol Amin; Amelia Rosanti; Firman Maulana; Muhammad Sulaiman Jazuli; Adinda Nur Atiqah (PT FORMOSA CENDEKIA GLOBAL, 2023)
The empowerment of Zero Waste Maritime Village Caring for the Marine Environment Based on Creative Economy was organized by the PPK Ormawa HMG Team, Lambung Mangkurat University, through socialization and education methods, training, and mentoring to the people of Wirittasi Village. With this program, the community can realize the potential of waste in Wirittasi Village. The activity results show that the district already has knowledge and skills in managing waste in Wirittasi Village through waste sorting activities and the 3R Movement. If continued, this program will improve the economic opinion of the community through waste management activities by the community. To maintain the program's sustainability, it is necessary to implement further programs, and the participation of village and local governments as facilitators for this community empowerment activity is needed.